Monitoramento do desempenho de diferentes tecnologias de módulos fotovoltaicos - BRAGA JÚNIOR, Wilson (Universidade Federal do Pará, 2014)
This work consists in an experimental analysis of 13 photovoltaic modules and 5 different technologies. For this, a test field for module measurement under real sun conditions was installed in the outdoor area of the Grupo de Estudos e Desenvolvimento de Alternativas Energéticas at the Universidade Federal do Pará, being the tests realized in the period between 21/10/2013 to 30/08/2013. Those measurements allowed the acquisition of the principal variables of interest of this kind of applicattion, which are: solar radiation, module temperature, module’s voltage, current and IV curve. With the obtained data was possible to evaluate the most important photovoltaic parameters such as efficiency, performance ration, productivity, among others. These quantities determine the generation characteristics of this kind of equipment and are very important to understand its operation; these quantities are presented in detail in graphical format throughout the text. In addition, this study brings other contributions, like the description of the system developed for the data processing, the experiences during the monitoring period, an overview of the state of art for photovoltaic modules and an analysis of the shading influence on the photovoltaic module’s performance.